Purification of Peroxidase from Latex of Euphorbia (Euphorbia amygdaloides) and Investigation of Kinetic Properties - ALAYLI GUNGOR, AZIZE; DEMIR, YASAR; DEMIR, NAZAN (Asian Journal of Chemistry, 2010)
The enzyme peroxidase was isolated from the latex of the Euphorbia (Euphorbia amygdaloides) and partially purified. The original extract (the supernatant) was purified by ammonium sulfate fraction, by CM-cellulose ion exchange chromatography and by Sepacryl S-100 gel filtration chromatography. The optimum pH value and the optimum temperature were determined pH: 6 and 40 ºC. The νmax and Km values were found 0.079 μmol/L/min and 0.26 mM, respectively. The purification degree and molecular weight were controlled by using SDS-PAGE. The enzyme was dimmer and composed with 23 kDa monomers. Then, the molecular weight of the enzyme was determined as 46 kDa using the gel filtration chromatography. It was investigated whether or not the purified enzyme can be used in the synthesis reaction. The activity of enzyme was measured in the different solvent. The results showed that methanol can be used to be a solvent for enzymatic reaction.